2017
DOI: 10.1007/s00705-017-3562-3
|View full text |Cite
|
Sign up to set email alerts
|

Serological and molecular markers of hepatitis E virus infection in HIV-infected patients in Brazil

Abstract: In Brazil, the circulation of hepatitis E virus (HEV) has been demonstrated in distinct groups of individuals and some animals, but its prevalence among individuals with human immunodeficiency virus (HIV) infection is unknown. This study aimed to assess the frequency of serological and molecular HEV markers in individuals infected with HIV from São Paulo, Brazil. Serum and plasma samples of 354 HIV-infected patients collected between 2007 and 2013 were included. All samples were tested for anti-HEV IgG and IgM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 58 publications
2
24
0
1
Order By: Relevance
“…The prevalence was considered to be average in comparison to the prevalence of HIV/HEV co-infection described worldwide, which varies from country to country and according to the methodology used. For example, the prevalence ranges from 0% to 4%: 0% in Brazil (Ferreira et al 2018). In our study, a viraemia of 3Á6% was found.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…The prevalence was considered to be average in comparison to the prevalence of HIV/HEV co-infection described worldwide, which varies from country to country and according to the methodology used. For example, the prevalence ranges from 0% to 4%: 0% in Brazil (Ferreira et al 2018). In our study, a viraemia of 3Á6% was found.…”
Section: Discussionsupporting
confidence: 47%
“…A recent study conducted in São Paulo, Brazil did not find any HEV RNA‐positive samples in 354 HIV‐positive patients (Ferreira et al . ). In our study, a viraemia of 3·6% was found.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A 10‐year gap in knowledge followed, until 2011, when studies from Argentina, Bolivia, Brazil and Colombia, reported respective HEV prevalences . This wave of studies followed the global reports of chronic hepatitis E virus infection by HEV‐3 in immunosuppressed individuals, especially those with solid organ transplantation as well as the reports of extra‐hepatic manifestations of HEV.…”
Section: Detection Of Hev In Humans In South Americamentioning
confidence: 99%
“…Brazil and Argentina are the only countries in South America which have reported studies about HEV circulation in immunocompromised populations (Table ) . In Argentina higher circulation of HEV was registered in HIV+ individuals, compared to blood donors (6.6% vs 1.8%), volunteers (35.7% vs 14.3% or 9.5%, depending on the kit used) and general population (7.3% vs 4.4%) .…”
Section: Detection Of Hev In Humans In South Americamentioning
confidence: 99%